PULSE WIDTH MODULATION TECHNIQUE FOR THE SPEED CONTROL OF M-PHASE AC MOTORS - EGWAILE JOEL OSARUMWENSE; ORIAHI MATTHEW (Journal of Engineering Studies and Research)
Thyristors are now widely used in many power electronics and motor driven applications and all the known methods of control are nothing but variations of either the phase angle firing control (PFC) or the pulse width modulation control (PWM). Each of these methods has its own benefits and disadvantages, but the pulse width modulation control method is, perhaps, by far, the most effective and costly method. Since PWM differs from phase firing control (PFC) in that the control action of PWM takes place only during the time of the firing pulse, this research seeks to develop a combination firing package that maximizes the benefits of the two methods. At first a thyristor is configured as a PNP-type power transistor latch with two ordinary NPN bipolar switching transistors. The power transistor is switched on by zero crossover firing and then switched off by phase angle delay firing. The performance of the model was evaluated and the dynamic characteristics of the motor, such as speed, current, voltage and the total harmonic distortion were carried via simulation. The results shows that by using the Modified PWM firing technique the speed of an m-phase induction motor can be controlled more effectively and reliably. The circuit is easy to implement and cost effective and may be patented and made available for commercial use.